THE IMPACT OF ROAD CONDITIONS ON THE SUSTAINABILITY DECLINE IN THE ROAD TRANSPORT IN THE REPUBLIC OF DAGESTAN - E. S. Batmanov; T. H. Gasanov; G. M. Guseynov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The article touches upon the theoretical and experimental studies of the influence of the various components of road conditions to reduce the stability of the vehicle, which lead to skidding and rollover. The resulting research material will improve traffic safety on the roads of the Republic of Dagestan. We give formulas for calculating the critical speed cornering with cross gradients and sharp change in direction, in which the skid and rollover is not excluded, due to the appearance of additional transverse forces of inertia. It is explained that a significant impact on the stability of the car has a «side pull». We give graphs of the lateral force from the vehicle slip angle of tires and tire tread wear of the impact on the quality of grip at different speeds and the amount of coating roughness obtained experimentally. Effect on the skid and rollover car road surface irregularities is marked. In such traffic conditions, the technical condition of the vehicle and in particular the shock absorbers are essential. The schedule damper effect on driving conditions, obtained experimentally.